2019
DOI: 10.3389/fpsyg.2018.02738
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Prospective Memory in Children: The Role of Cue Focality

Abstract: Prospective memory (PM) is an essential ability in daily life, since it involves remembering to perform an intention. While PM largely develops during childhood and adolescence, its underlying mechanisms are still poorly understood. In general, age differences in PM have been found with tasks in which the prospective cues are not part of the ongoing activity (non-focal PM tasks). In the present study, we evaluated the cognitive cost produced by a PM task over the ongoing activity by comparing the performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…We therefore ran an unplanned model including the squared age term to look for evidence of nonlinearity. The effect was marginally significant for nonfocal tasks, B = .0004 [−0.000, .0008], t = 1.88, p = .06, and further inspection confirmed a notable outlier likely having undue influence (a nonfocal effect size with children aged 11 was d = 2.90; Cejudo et al, 2019). Removal of this outlier eliminated all previously reported age effects.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…We therefore ran an unplanned model including the squared age term to look for evidence of nonlinearity. The effect was marginally significant for nonfocal tasks, B = .0004 [−0.000, .0008], t = 1.88, p = .06, and further inspection confirmed a notable outlier likely having undue influence (a nonfocal effect size with children aged 11 was d = 2.90; Cejudo et al, 2019). Removal of this outlier eliminated all previously reported age effects.…”
Section: Resultsmentioning
confidence: 94%
“…A follow-up linear combination test further showed that the difference in costs between focal and nonfocal tasks was marginally significant, z = 1.88, p = .06. We suspected that this trend could reflect the influence of children and adolescents, reasoning that nonfocal tasks may be especially difficult for children because their frontal lobes are not fully developed (Cejudo, Gómez-Ariza, & Bajo, 2019). We therefore ran an unplanned model including the squared age term to look for evidence of nonlinearity.…”
Section: Resultsmentioning
confidence: 99%
“…The current findings suggest that for these children, the ability to monitor or rehearse the PM intention is still developing and therefore therapeutic support (i.e. providing salient cues) has the potential to improve their ability to follow instructions (and organisation) in everyday life (Cejudo et al, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, the potential challenges associated with maintaining a prospective intention while conducting an OT appear to be greater for a nonfocal PM task (cf. Cejudo et al, 2019 ). Current evidence suggests that children are more successful in performing focal tasks at an earlier stage of life compared to nonfocal tasks (however, see Kelly et al, 2023 , for contrary findings).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we analyzed children’s monitoring during the OT in both focal and nonfocal tasks. Monitoring in PM is typically analyzed by comparing reaction times in OTs between different PM and control (no PM task) conditions, with monitoring costs measured as slower reaction times in PM conditions (e.g., McDaniel et al, 2011 ; Chi et al, 2014 for adults studies; Cejudo et al, 2019 for children study). Cejudo et al (2019) conducted a study on children’s performance in a control condition, and compared it with performance in two PM conditions that varied in cue focality.…”
Section: Introductionmentioning
confidence: 99%